2023
DOI: 10.1186/s12951-023-01781-x
|View full text |Cite
|
Sign up to set email alerts
|

Renal clearance of graphene oxide: glomerular filtration or tubular secretion and selective kidney injury association with its lateral dimension

Abstract: Background Renal excretion is one of the major routes of nanomaterial elimination from the body. Many previous studies have found that graphene oxide nanosheets are excreted in bulk through the kidneys. However, how the lateral size affects GO disposition in the kidneys including glomerular filtration, active tubular secretion and tubular reabsorption is still unknown. Results The thin, two-dimensional graphene oxide nanosheets (GOs) was observed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…40–45 Meanwhile, in vivo studies performed with animal models have shown that GRMs tend to accumulate throughout the organism, mainly in the liver, lungs, spleen and kidney, thus resulting in varying degrees of damage to these organs. 46–52…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…40–45 Meanwhile, in vivo studies performed with animal models have shown that GRMs tend to accumulate throughout the organism, mainly in the liver, lungs, spleen and kidney, thus resulting in varying degrees of damage to these organs. 46–52…”
Section: Resultsmentioning
confidence: 99%
“…To confirm these results, a renal proximal tubular cell line (HK-2) was used and the uptake of l-GO was found to be higher than s-GO after 4 and 24 hours of graphene exposure for HK-2 cells in traditional cell culture. 49…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detoxifying enzyme catalase was decreased whereas levels of the oxidative stress marker malondialdehyde were increased in tissue homogenates. Both GO dose and lateral dimension affected renal excretion pathways and kinetics as well as extent of kidney injuries in CD1 mice . The small GO materials (162 nm) were eliminated via glomerular filtration and induced structural alterations in glomerular podocytes while larger GO materials (330 nm) were eliminated faster via the proximal tubules.…”
Section: Impact On Liver Spleen and Kidneysmentioning
confidence: 99%
“…Both GO dose and lateral dimension affected renal excretion pathways and kinetics as well as extent of kidney injuries in CD1 mice. 304 The small GO materials (162 nm) were eliminated via glomerular filtration and induced structural alterations in glomerular podocytes while larger GO materials (330 nm) were eliminated faster via the proximal tubules. At 15 mg/kg and both 2 and 7 days, both materials injured renal tubular epithelial cells, causing loss of brush border, cast formation and tubular dilatation, as well as increased glomerular diameter.…”
Section: Impact On Liver Spleen and Kidneysmentioning
confidence: 99%